Role of Antioxidant Gene Polymorphisms in Risk and Prognosis of Chronic Myeloid Leukemia - Sailaja Kagita; Raghunadharao Digumarti; Sadhashivudu Gundeti (Asian Pacific Journal of Cancer Biology, 2021)
Introduction: We aimed to investigate the possible role of antioxidant enzyme polymorphisms CAT -21A/T (rs7943316), CAT -262C/T (rs1001179), GPX1 -198C/T (rs1050450), MPO -463G/A (rs2333227), GSTM1 (rs366631) & GSTT1 (rs17856199) with susceptibility to chronic myeloid leukemia (CML) and their association with tyrosine kinase inhibitor (TKI, imatinib) response. Methods: Six single nucleotide polymorphisms (SNPs) in antioxidant enzyme genes were genotyped in a total of 325 samples, of which 125 were from CML patients and 200 from healthy controls. The SNPs were correlated with various confounding variables lke BCR-ABL1 levels and tyrosine kinase domain mutation status in CML patients. Results: Genotyping results revealed statistically significant associations with CAT -21A/T (p=0.037) and GPX1 -198C/T (p=<0.0001) polymorphisms with risk of CML. No associations were observed between CAT -262C/T, MPO -463G/A, GSTM1 & GSTT1 polymorphisms and CML. The CAT -21A/T polymorphism conferred 2.95 folds increased risk of CML under co-dominant model (p=0.024) and 2.51 folds risk under dominant models (p=0.05). In addition, the haplotypes of CAT -21A/T and -262C/T polymorphisms, ATCC and ATCT conferred higher incidence of CML risk by 2.67 times (p=0.05) and 2.99 times (p=0.045). The GPX1 -198C/T polymorphism conferred significantly increased risk of CML under co-dominant model [CC vs CT (p=<0.0001), CC vs TT (p=<0.0001)] and dominant models [CC vs CT+TT (p=<0.0001)]. The heterozygous GPX1 CT genotype frequency significantly elevated in poor molecular responders (p=0.005) and TKD mutation carriers (p=0.114) as compared to respective groups. Conclusions: Our results suggest that the reduced activity of antioxidant enzymes caused by the CAT -21A/T and GPX1-198C/T polymorphisms might contribute to increased risk of CML. In addition, the GPX1-198C/T polymorphism was associated with poor molecular response and acquired TKD mutations. Hence, the present study indicates that defective antioxidant defense system might have a strong influence on CML susceptibility and TKI (imatinib) response through oxidative stress.